"S^{2}=\\frac{1}{n-1}(\\sum x^{2}-\\frac{(\\sum x)^{2}}{n})\\\\\n\\text{For the first sample n=10}\\\\\nS_{1}^{2}=\\frac{1}{9}(20^{2}+16^{2}+...+19^{2}-\\frac{(20+16+...+19)^{2}}{10})\\\\\n=13.33\\\\\n\\text{For the second sample n=12}\\\\\nS_{2}^{2}=\\frac{1}{11}(27^{2}+33^{2}+...+37^{2}-\\frac{(27+33+...+37)^{2}}{12})\\\\\n=28.55\\\\\nS_{p}^{2}=\\frac{(n_{1}-1)S_{1}^{2}+(n_{2}-1)S_{2}^{2}}{(n_{1}+n_{2}-2)}\\\\\nS_{p}^{2}=\\frac{(9)(13.33)+(11)(28.55)}{20}\\\\\n=21.701"
Comments
Leave a comment